An overview of the meningococcal disease and impact of the quadrivalent meningococcal conjugate vaccine - Asmaa Alrobai; Jehan Alrahimi; Sahar El Hadad (Novel Research in Microbiology Journal)
Meningitis is an inflammation of the meninges, which are the three membranes that cover the brain and the spinal cord; which occurs when the fluid surrounding the meninges becomes infected. Meningitis is a life-threatening disease, particularly in older people and immunocompromised cases. The estimated annual numbers of meningitis cases in the industrialized countries are about 4-6 cases per 100,000 people. Meningococcal disease is caused by the bacterium Neisseria meningitides, which have A; C, Y, and W-135 serogroups. Immunization helps to protect the humans from infection, such as the meningococcal vaccine that protects from infection by A; C, Y, and W-135 serogroups. Meningococcal conjugate vaccines improve the immunogenicity potential, to prevent meningococcal disease. Several previous studies have documented the decrease in post-vaccination effectiveness induced by the meningococcal vaccines. However, effectiveness requires revaccination after a period of time from the first vaccination. The purposes of this article were to provide an overview of the meningitis disease, and demonstrate the effectiveness of the meningococcal conjugate vaccine.